MIBiG 4.0: advancing biosynthetic gene cluster curation through global collaboration - Zdouc, Mitja M; Blin, Kai; Louwen, Nico L L; Navarro, Jorge; Loureiro, Catarina; Bader, Chantal D; Bailey, Constance B; Barra, Lena; Booth, Thomas J; Bozhüyük, Kenan A J; Cediel-Becerra, José D D; Charlop-Powers, Zachary; et al. (Nucleic acids research, 2025)
Specialized or secondary metabolites are small molecules of biological origin, often showing potent biological activities with applications in agriculture, engineering and medicine. Usually, the biosynthesis of these natural products is governed by sets of co-regulated and physically clustered genes known as biosynthetic gene clusters (BGCs). To share information about BGCs in a standardized and machine-readable way, the Minimum Information about a Biosynthetic Gene cluster (MIBiG) data standard and repository was initiated in 2015. Since its conception, MIBiG has been regularly updated to expand data coverage and remain up to date with innovations in natural product research. Here, we describe MIBiG version 4.0, an extensive update to the data repository and the underlying data standard. In a massive community annotation effort, 267 contributors performed 8304 edits, creating 557 new entries and modifying 590 existing entries, resulting in a new total of 3059 curated entries in MIBiG. Particular attention was paid to ensuring high data quality, with automated data validation using a newly developed custom submission portal prototype, paired with a novel peer-reviewing model. MIBiG 4.0 also takes steps towards a rolling release model and a broader involvement of the scientific community. MIBiG 4.0 is accessible online at https://mibig.secondarymetabolites.org/.
Keywords: Databases, Genetic; Multigene Family; Molecular Sequence Annotation; Biological Products; biologické přípravky; Biosynthetic Pathways; biosyntetické dráhy; Data Curation; databáze genetické; multigenová rodina; anotace sekvence; datové kurátorství